Novi najdbi v slovenski favni metuljev (Lepidoptera) - Štanta, Radovan (Acta entomologica slovenica (Ljubljana), 2008)
In West Slovenia two new Lepidoptera species in the Slovenian fauna were verified: Acanthopsyche ecksteini Lederer, 1855 (Psychidae) and Paralipsa gularis Zeller, 1877 (Pyralidae). A. ecksteini was found near Opatje selo on Goriški Kras, in a small dry and hot calcareous grassland and shrubbery area. Several larvae in cases were observed in the beginning of September 2006, feeding on Satureja montana L., Genista germanica L. and Dorycnium germanicum (G.) R. During the emergence of the adults in April 2007 we noticed that female pheromone attracts also the males of a relative species Acanthopsyche zelleri Mann, 1855 for a short time. One male specimen of P. gularis was found in Miren, Vipava valley, on June 4, 1995.
Keywords: entomologija; favna; metulji; nove najdbe; Slovenia; Slovenija